Can one die because of Hashimoto’s disease? – a clinical review of diagnosis, clinical features and treatment of myxedema coma - Bochyński, Karol; Dacka, Michał; Giżewska, Kamila; Białogłowski, Konrad; Dąbrowska, Paulina; Żuber, Michał; Ciuba, Katarzyna; Molenda, Katarzyna; Borodziuk, Filip; Borodziuk, Barbara (Quality in Sport, 2024)
Introduction and Purpose Hashimoto’s disease is the most common reason of hypothyroidism. Usually, it is easy to recognize and treat. However, under certain circumstances, it may develop into the most severe manifestation of hypothyroidism known as myxedema and can lead to a threat to the patient's life. Hypothyroid crisis, or myxedema coma, is an extremely rare but fatal medical emergency. If the condition is not promptly diagnosed and treated, the mortality rate is high as 50%. Even with immediate recognition and appropriate medical intervention, mortality rates of up to 25% have been observed. This article aim is to enhance medical community awareness by examining features of myxedema, prevalence, and associated risk factors, contributing to improved clinical management. Emphasizing tailored treatment strategies for hypothyroidism, coexisting illnesses, and metabolic decompensation, it ultimately seeks to enhance outcomes for patients with severe hypothyroidism. Material and methods Conducting a systematic review of medical articles from 1997 to 2024 using PubMed, this study analyzed articles with keywords such myxedema coma, hypothyroidism, Hashimoto’s thyroiditis. Inclusion of pertinent articles ensured a comprehensive exploration of myxedema coma literature during the specified time frame. Summary Myxedema coma is a thyroid emergency linked to hypothyroidism. This review sheds light on the etiology of myxedema, clinical manifestations, diagnostic criteria and comprehensive treatment options. In order to reduce mortality in patients, there is a need to increase knowledge of the risk of development, clinical features and management not only for emergency physicians but also for physicians of all specialties..